Classroom management and leadership styles of kindergarten teachers of Schools Division of Pangasinan II - Castro, Grace P. (Panpacific University : [s.n.], 2021)
Classroom management necessitates the involvement of a wide variety of skills and techniques that teachers use to keep learners focused, organized and productive. It is something that each individual teacher gradually develops to increase learning. The study revolves around the practice of classroom management by kindergarten teachers. Their leadership styles are identified and the relationship of each leadership style with the four-fold management components of planning, leading, organizing and controlling are also determined. The responses of the school administrators are used to validate the kindergarten teachers' responses through defining the significant difference. In general, the kindergarten teachers significantly differ in terms of the extent of practice in classroom management with that of the school administrators. On the other hand, the school administrators significantly rated higher in their practice of the four-fold management components. Consequently, a proposed classroom management enhancement plan is created along the management components as the key result areas.
References: pages 113-121.
CHED-La Union
Keywords: Classroom management